Didattica generale: ambiti di intervento e struttura epistemologica - Giuliano Franceschini (Firenze University Press, 2020)
In this article we present some definitions of didactics and analyze the relationship between general didactics and specialized didactics. The aim is to provide a reference framework useful for reading the epistemological structure of the didactic discourseAfter a first section dedicated to the definition of teaching as a science of education, we move on to a second section dedicated instead to the analysis of the relationship between general teaching and specialized teaching. The article concludes with a reflection on the importance of critical teaching, understood as an analysis of the relationships between internal factors and factors external to the training event.